Research on elevated orbit noise propagation based on AI algorithm and propagation path analysis - Ling-Xiao, Weng; Xiao-Yan, Lei; Kun, Luo (Frontiers in Physics, 2023)
With the rapid development of high-speed railway, noise reduction is becoming more and more important. This article aims to investigate the analysis of the vibration and noise transmission path of the elevated railway. An optimized transmission path analysis method, which is based on the artificial intelligence algorithms, is used to optimize the path analysis, so as to trace the source of the noise and analyze the noise reduction. This method performs well in the analysis of vibration and noise of elevated railways. After this optimization, the contribution degree and frequency response function in the path analysis have better analysis performance. Through the actual measurement and analysis of the noise of the elevated railway, it can be proved that the traditional path method can better analyze the noise source. Wheel/rail noise, pantograph noise, and aerodynamic noise are the main noise sources. The environmental noise caused by high-speed trains passing bridges easily exceeds the acoustic environmental standards. After noise reduction, it can be reduced by about 5-10 decibels.